ASSESSMENT OF GROUNDWATER RESOURCES IN THE DENSU RIVER BASIN OF SOUTHERN GHANA (Journal of Science and Technology, 2016)
Groundwater resources in the Densu River Basin in southern Ghana have been evaluated through detailed assessment of borehole data and information. Geologically, three formations underlie the basin: Granitic Rocks, the Togo Series and Upper Birimian Formation.  Aquifer regimes occur in semi-confined and confined fractured reservoirs and are encountered at a mean depth of 17.9 m. In the granite, borehole yields vary between 1.7 and 1200.0 lmin-1.  The mean yield is 32.5 lmin-1. The specific capacity ranges from 0.4 to 75.3 m2day-1, which indicates that the groundwater potential varies from very low to intermediate levels. The transmissivity varies from 0.5 to 86.8 m2day-1, characteristic of fairly heterogeneous hydrogeological environment. The yield of boreholes in the Togo Series ranges from 10.0 to 100.0 lmin-1, with a mean value of 46.5 lmin-1. For the Upper Birimian Formation, the yield ranges from 12.0 to 150.0 lmin-1, with an average yield of 61.2 lmin-1.  Although groundwater potential is generally low in the basin, considerable reserves of acceptable quality are available for specific uses. Concerted efforts are therefore needed to identify zones of intense fracturing and advanced weathering to locate potential sites where groundwater can be exploited in larger quantities. The tectonic contact zone between the quartzite and schist of the Togo Series, and the granite at the western flanks of the Akwapim-Togo Ranges is a potential groundwater discharge area. For sustainable groundwater use, measures for groundwater protection against over-exploitation and pollution are needed, especially in those areas where groundwater is being commercially exploited.